Minimalist-Design Folded-Back Architecture-Based Linear Optical Frequency Discriminator (LOFD) for Microwave Photonics Link (MPL) - Dingel, Benjamin (Archīum Ateneo, 2021)
This paper has four goals. Firstly; we present; for the first time to the best of our knowledge; a minimalist-design; Linear Optical Electric Field Frequency Discriminator (LOEF-FD) for Microwave Photonic Link (MPL) using only a single Mach-Zehnder Interferometer (MZI) configured in unique folded-back arrangement. The standard configuration of LOEF-FD requires two MZI elements in serial arrangement with additional interferometric arm. The original minimalistdesign structure was first proposed by our group and used as an active device known as linear optical field modulator (LOFM) [8]. Here; we use it as a passive LOEF-FD for MPL application. Secondly; we layout the benefits of the new design such as: (i) reduced chip footprint; (ii) decreased component cost by one-half; and (iii) avoidance of the troublesome engineering problem associated with perfectly matching of the two MZIs in the original design. However; due to the folded-back architecture of the new simplified LOEF-FD; we need to be attentive to the negative impact of the back-reflected electric field on the overall linearity of the frequency discriminator. Thus; for our third goal; we investigated and quantified its effect on the (i) amplitude linearity; (ii) bandwidth; (iii) phase response; and (iv) group delay. We show that a 5% back reflection from the final output reduces the performance of the ideal LOEF-FD’s effective bandwidth utilization (BWU) by about 10%. Lastly; we present a common mitigated scheme to reduce the back reflection.